Maternofoetal Complications and Their Association with Proteinuria in a Tertiary Care Hospital of a Developing Country. (13th April 2014) - Kumari, Archana; Chakrawarty, Avinash; Singh, Abha; Singh, Ritu
Abstract : Objective . To investigate association between maternofoetal complications and the amount of proteinuria measured by spot urine protein creatinine ratio in patients with preeclampsia. Methods . 200 consecutive patients with preeclampsia were recruited in the study. The complications like first episode of severe hypertension, renal insufficiency, raised level of aspartate transaminase, signs of neurological involvement, thrombocytopenia, eclampsia, and need to shift in intensive care units were studied. The maternal outcome was studied in terms of type of labour, outcome of pregnancy, mode of delivery, indication of cesarean section, and maternal mortality. The foetal complications and outcome parameters were birth weight, Apgar score at the time of birth and at five minutes, need of high dependency unit care, and perinatal mortality. Result . The frequency of various maternal and foetal complications was between 14–53% and 22–92%, respectively. Maternal mortality was 3%, whereas perinatal mortality was 23%. Statistically significant association was found between the frequencies of various complications in mother and newborn and spot UPCR. Conclusion . The rate of various maternofoetal complications in preeclampsia is higher in developing countries than in developed world. Maternofoetal complications and outcome correlate with maternal spot UPCR.